Cell size as driver and sentinel of phytoplankton community structure and functioning. (23rd December 2021) - Hillebrand, Helmut; Acevedo‐Trejos, Esteban; Moorthi, Stefanie D.; Ryabov, Alexey; Striebel, Maren; Thomas, Patrick K.; Schneider, Marie‐Luise
Abstract: Body size is a decisive functional trait in many organisms, especially for phytoplankton, which span several orders of magnitude in cell volume. Therefore, the analysis of size as a functional trait driving species' performance has received wide attention in aquatic ecology, amended in recent decades by studies documenting changes in phytoplankton size in response to abiotic or biotic factors in the environment. We performed a systematic literature review to provide an overarching, partially quantitative synthesis of cell size as a driver and sentinel of phytoplankton ecology. We found consistent and significant allometric relationships between cell sizes and the functional performance of phytoplankton species (cellular rates of carbon fixation, respiration and exudation as well as resource affinities, uptake and content). Size scaling became weaker, absent or even negative when addressing C‐ or volume‐specific rates or growth. C‐specific photosynthesis and population growth rate peaked at intermediate cell sizes around 100 µm 3 . Additionally, we found a rich literature on sizes changing in response to warming, nutrients and pollutants. Whereas small cells tended to dominate under oligotrophic and warm conditions, there are a few notable exceptions, which indicates that other environmental or biotic constraints alter this general trend. Grazing seems a likely explanation, which we reviewed to understand both how size affects edibility and how size structure changes in response to grazing. Cell size also predisposes the strength and outcome of competitive interactions between algal species. Finally, we address size in a community context, where size‐abundance scaling describes community composition and thereby the biodiversity in phytoplankton assemblages. We conclude that (a) size is a highly predictive trait for phytoplankton metabolism at the cellular scale, with less strong and nonlinear implications for growth and specific metabolism and (b) size structure is a highly suitable sentinel of phytoplankton responses to changing environments. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.